Penerapan Konsep Teori Utilitarianisme Dalam Penegakan Hukum Di Indonesia - Nurwidya Kusma Wardhani; Tulus M. Lumban Gaol; Taufiqurrohman Syahuri (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to see how the concept of utilitarianism is applied in Indonesia. The application of the theory of utilitarianism will be studied more deeply in terms of law enforcement in society. Of course, through this method it can be seen that utilities that are useful and benefit the whole community will have more value than a legal decision that only benefits each party. One figure, Jeremy Bentham, said that the aim of law must fulfill three aspects, namely Justice, Certainty and Benefit. Therefore, legal objectives must be met so that the regulations or legal products formed by law bearers are expected to fulfill these three aspects perfectly. However, the truth of these three aspects as the objectives of creating a legal product that must exist, must be examined more deeply, whether it is true that the law has perfectly created justice, has certainty, and must provide benefits to society. The data collection method was carried out by studying literacy and statutory regulations and conducting qualitative descriptive data analysis.